Letter from Kathleen Raine to Percy Jarrett, February 02, [1974] - http://id.worldcat.org/fast/52672 (1974)
Part of a collection of letters from award-winning British poet and scholar Kathleen Raine to Percy Jarrett, owner of the dealership Philobiblion which specialized in literary books and manuscripts. Most of the letters discuss the negotiation of sales of Raine’s manuscript material (of which Irvine Library at the University of California was the primary buyer), the periodical Temenos, that Raine co-founded; and Jarret’s son-in law Robin Skelton, who was a poet and Professor of English Literature at the University of Victoria.